The effect of surfactants-bound magnetite (Fe3O4) on the photocatalytic properties of the heterogeneous magnetic zinc oxides nanoparticles - Feng, Xiaohui; Lou, Xia (Pergamon Press, 2015)
The article reports the synthesis and characterisation of two new magnetite (Fe3O4)-supported zinc oxide (ZnO) photocatalysts, produced in the presence of Fe3O4 nanotemplates that were bound with tetramethylammonium (TMAH) and citric acid (CA) respectively. The TMAH-bound hybrid nanoparticles, Fe3O4(TMAH)–ZnO, have demonstrated a high recoverability (86%) and phenol degradation rate constant of 0.0170 min−1, which is much greater than that of the CA-bound photocatalyst (0.0085 min−1) and the pure form of ZnO (0.0039 min−1). Further investigation demonstrates that the presence of various surfactants on the surface of the magnetite nano-templates significantly affects the size, the surface and the optical properties of the produced hybrid nanophotocatalysts, and subsequently their photocatalytic activities. The pH values of the photocatalysis environment also show strong influences to the photocatalytic properties and the dissolution of the nanoparticles. An optimal operation condition for the Fe3O4(TMAH)–ZnO is when the photocatalysis is carried out at a pH = 4–5.6, and the concentrations of the photocatalyst and phenol are 325 and 20 mg L−1, respectively.